2023
DOI: 10.1001/jamanetworkopen.2023.9995
|View full text |Cite
|
Sign up to set email alerts
|

Social Vulnerability and Risk of Suicide in US Adults, 2016-2020

Abstract: ImportanceThere were over 45 000 suicides in the US in 2020, making suicide the 12th leading cause of death. If social vulnerability is associated with suicide rates, targeted interventions for at-risk segments of the population may reduce US suicide rates.ObjectiveTo determine the association between social vulnerability and suicide in adults.Design, Setting, and ParticipantsThis cohort study analyzed 2 county-level social vulnerability measures (the Social Vulnerability Index [SVI] and the Social Vulnerabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…For example, a 2017 study from Korea showed that people with lower household income were at a higher risk of suicide, and that this rate increased across income deciles, so that people in the lowest income decile had more than three times the suicide risk of people in the highest income decile [57]. A 2023 study from the United States found that higher county-level social vulnerability (measured by the Social Vulnerability Metric which incorporates socioeconomic factors such as county-level average unemployment, education, insurance, and housing) was associated with a higher suicide rate [58].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 2017 study from Korea showed that people with lower household income were at a higher risk of suicide, and that this rate increased across income deciles, so that people in the lowest income decile had more than three times the suicide risk of people in the highest income decile [57]. A 2023 study from the United States found that higher county-level social vulnerability (measured by the Social Vulnerability Metric which incorporates socioeconomic factors such as county-level average unemployment, education, insurance, and housing) was associated with a higher suicide rate [58].…”
Section: Discussionmentioning
confidence: 99%
“…Our primary independent variable was zip code level estimates of the SVM . The SVM builds on existing SV measures by weighting the set of included neighborhood characteristics using multi-dimensional item response theory, which leverages item difficulty and item-test correlations.…”
Section: Methodsmentioning
confidence: 99%
“…Our study investigates associations between the Social Vulnerability Metric (SVM), a new measure of SV that expands on previous measures through the use of item-level weighting, with MH and SUD prevalence and treatment use. Our primary research objective was to determine the ability of the SVM to reflect the prevalence of local MH and SUD as assessed by MH clinicians using a structured clinical interview and to identify unmet service needs for specific behavioral health indications.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, research has consistently shown that increasing the minimum wage lowers suicide rates ( 31 ). Kaufman and colleagues estimated that in the US, raising the minimum wage by just USD $1.00 above the levels from 1990 to 2015 would have saved 27,550 suicide deaths ( 32 ) (see also, 33 ). Such findings are why the former United Nations Special Rapporteur, psychiatrist Dainius Puras, called for addressing the social determinants of health rather than simply “scaling up” the diagnosis and treatment of depression based on prevailing reductionist approaches ( 34 , 35 ).…”
Section: Foundations Of Wellbeingmentioning
confidence: 99%